2020
DOI: 10.3390/ani10040598
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence Reveals Both Cross-Infection and Cross-Contamination Risk of Embryo Storage in Liquid Nitrogen Biobanks

Abstract: In recent decades, gamete and embryo cryopreservation have become routine procedures in livestock and human assisted reproduction. However, the safe storage of germplasm and the prevention of disease transmission continue to be potential hazards of disease transmission through embryo transfer. This study aimed to demonstrate the potential risk of cross-infection of embryos from contaminated liquid nitrogen, and cross-contamination of sterile liquid nitrogen from infected embryos in naked and closed devices. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Initially they were stored in an open device (Cryotop, Kitazato). In this regard, it should be noted that there is a risk of both cross-infection and cross-contamination of embryos and gametes in liquid nitrogen tanks [8] .…”
Section: Discussionmentioning
confidence: 99%
“…Initially they were stored in an open device (Cryotop, Kitazato). In this regard, it should be noted that there is a risk of both cross-infection and cross-contamination of embryos and gametes in liquid nitrogen tanks [8] .…”
Section: Discussionmentioning
confidence: 99%
“…Although no case exists within the human IVF community of cross-contamination during the course of cryostorage, research has demonstrated that cross-contamination does pose a real risk [ 45 , 46 ]. If we accept that the SARS-CoV-2 virus can be detected in the semen and the virus is resistant to liquid nitrogen, as is the case with many other viruses, maybe additional specific measures should be followed to minimize the presence of the virus during sperm cryopreservation and any possible cross-contamination effect.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the similar success rates in open IVF using frozen oocytes and fresh oocytes, asepsis-related problems have been observed due to cross-contamination between vitrificated oocyte samples and microorganisms in liquid nitrogen [ 87 , 88 , 89 ]. To solve this issue and minimize surrounding contaminants, liquid nitrogen was sterilized using UV light, or additional pretreatment was applied [ 89 , 90 ]. However, due to the difficulty of implementing a perfectly aseptic system, in-straw vitrification was developed.…”
Section: Technical Problems and Solutions Of Cryopreservation Of Game...mentioning
confidence: 99%